The impact of caring for a child with cerebral palsy: Quality of life for mothers and fathers - Davis, E.; Shelly, A.; Waters, E.; Boyd, Roslyn; Cook, K.; Davern, M. (Blackwell Publishing Ltd, 2010)
Background: Although it is expected that caring for a child with cerebral palsy (CP) can impact on the quality of life (QOL) of caregivers, the QOL of carers' has yet to be adequately examined. The aims of this study are to: (1) explore the QOL of mothers and fathers of children with CP aged 3-18 years; and (2) examine whether the impact of caring for a child with CP changes from childhood to adolescence. Method: A qualitative study was conducted utilizing a grounded theory framework. Twenty-four mothers and 13 fathers of children and adolescents with CP aged 3-7 years (n = 15), 8-12 years (n = 10) and 13-18 years (n = 12) and with varying levels of impairment (GMFCS Level I = 1, II = 4, II = 3, IV = 5, V = 12) participated in semi-structured interviews about their QOL. The transcripts were analysed to identify issues affecting parental QOL. Results: There were no differences in parental QOL among subgroups (i.e. mothers and fathers, age groups, GMFCS levels). Parental QOL ranged across a wide spectrum. Caring for a child with CP affects a parent's physical well-being, social well-being, freedom and independence, family well-being and financial stability. Parents indicated that they often feel unsupported by the services they access. Conclusions: Caring for a child with CP can both positively and negatively impact on a parent's life. There is value for both parents and children if parental concerns and determinants of QOL are considered in overall programme planning and service delivery for children and their families. © 2009 The Authors. Journal compilation © 2009 Blackwell Publishing Ltd.